A Kimmeridgian (Upper Jurassic) source for early Roman yellow tesserae and opus sectile in southern Britain - ALLEN, J. R. L.; TODD, Jan (Britannia, 2010)
Examination of pieces of yellow burnt mudstone from a builder's yard in the villa at Fishbourne (West Sussex) strongly indicates procurement from the Kimmeridge Clay Formation of the Poole-Purbeck area of Dorset. This material was widely used in southern Britain in the early Roman period in the production of opus sectile and tessellated mosaic, e.g., at Silchester (Hampshire), Caerleon (Monmouthshire) and Eccles (Kent), as was a red burnt mudstone derived from the same source.
p. 317-321.
Keywords: Études techniques; Analyse pétrographique; Opus sectile; Géologie; Villa (Fishbourne, GBR); Caerleon; Eccles; Fishbourne; Grande-Bretagne; Silchester